Mengapa Yesus Kristus Layak Disembah? Kajian Etika Teologis - Jamin Tanhidy; Julian Kerli Jangin; Bayu Rahma Wijaya; Friskila Friskila (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2025)
Worship of Jesus is the core of the Christian faith, distinguishing it from other religions, based on the belief in the Bible of His divinity as the incarnate Word of God. He has two natures (dual nature), namely as true God and true man. He came to the world to save humanity from the death penalty due to sin. However, there are still many issues of understanding and theological interpretation related to the dual nature of Christ, such as the rejection from Jehovah's Witnesses, Gnostics, and Islamic polemics. This rejection of the dual nature often leads to the rejection of worshiping Jesus. Through a literature review with a theological ethics approach, this research analyzes biblical verses, particularly the Gospels and the letters of Paul, as well as scientific literature, to find the theological-ethical reasons why Jesus Christ is worshiped. The study results show that Jesus Christ is worthy of worship because He is the Lord and Savior of humanity, He receives worship from humans, and He is worshipped by angels. The theological implication is the affirmation of the doctrine of salvation and the Trinity as the basis for worshiping Christ, while the ethical implication is that His people are required to have a holy life, serve, and have eschatological hope.